Pelatihan Pembuatan Pemodelan Dan Simulasi Banjir Di Kawasan Pesisir Kota Semarang Menggunakan ArcScene 10.4 - Tiasa Adimagistra; Rizqy Ridho Prakasa; Wahjoerini Wahjoerini (Universitas Semarang, 2023)
In the field of regional and urban planning, several media can be used to convey information about the problems of an area. The most commonly used medium is using maps. The analysis carried out to present information in the form of maps varies according to needs. To represent and present flood and tidal information in the coastal area of Semarang City, 3D modeling training was conducted using ArcScene 10.4 software, which is part of ArcGIS software. This modeling is carried out by utilizing DEM (Digital Elevation Model) data and data on the addition of water discharge in coastal areas which will then be processed and simulated in the 3-dimensional form that can be watched in video form. It is hoped that this community service in the form of training can provide further knowledge and understanding regarding mapping activities so that it can be applied in student learning and research activities. So second-semester students of the Urban and Regional Planning Department, Faculty of Engineering, Universitas Semarang have a basic understanding of planning and a more sensitive to urban issues and how to do the right analysis according to the goals and needs of urban planning.